2017
DOI: 10.18632/oncotarget.16467
|View full text |Cite
|
Sign up to set email alerts
|

Role of EZH2 in cancer stem cells: from biological insight to a therapeutic target

Abstract: Epigenetic modifications in cancer stem cells largely result in phenotypic and functional heterogeneity in many solid tumors. Increasing evidence indicates that enhancer of zeste homolog 2 (EZH2), the catalytic subunit of Polycomb repressor complex 2, is highly expressed in cancer stem cells of numerous malignant tumors and has a critical function in cancer stem cell expansion and maintenance. Here, we review up-to-date information regarding EZH2 expression patterns, functions, and molecular mechanisms in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 133 publications
0
51
0
1
Order By: Relevance
“…Our previous study found that hnRNPK regulates diverse functions in bladder cancer by directly mediating transcription of target genes; however, the detailed mechanism remained unclear (24). EZH2, a histone methyl transferase subunit of the polycomb repressor complex 2 (PRC2), is an oncogene that is central to tumor proliferation, metastasis, and self-renewal (40,41). In the present study, we found that lnc-LBCS physically interacts with hnRNPK and EZH2, and lnc-LBCS serves as a scaffold to induce the formation of hnRNPK-EZH2 complex.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that hnRNPK regulates diverse functions in bladder cancer by directly mediating transcription of target genes; however, the detailed mechanism remained unclear (24). EZH2, a histone methyl transferase subunit of the polycomb repressor complex 2 (PRC2), is an oncogene that is central to tumor proliferation, metastasis, and self-renewal (40,41). In the present study, we found that lnc-LBCS physically interacts with hnRNPK and EZH2, and lnc-LBCS serves as a scaffold to induce the formation of hnRNPK-EZH2 complex.…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 is upregulated in many cancers and its enhanced expression of EZH2 is associated with invasion, migration and stemness (Yamaguchi and Hung 2014). In breast cancer, overexpression of EZH2 has increased mammosphere formation and self-renewal ability in breast CSCs (Chang, Yang et al 2011, Wen, Cai et al 2017. In glioblastoma, loss of H3K27me3 leads to aberrant activation of a transcription factor, ASCL1 and results in Wnt activation which is required for tumorigenicity and CSC maintenance (Rheinbay, Suva et al 2013).…”
Section: Mechanisms Controlling Csc Plasticitymentioning
confidence: 99%
“…Ezh2 belongs to the polycomb repressive complex 2 (PRC2), which participates in methylation of histone 3 (H3K27me) leading to transcriptional repression (33,34). Ezh2 has been described to have an important role in coordinating cell differentiation in embryonic stem cells (35,36), mesenchymal stem cells (37-39), hematopoietic stem cells (40,41), and also in various types of cancer (42,43). Inhibition of Ezh2 has been reported to prevent renal fibroblast activation (44), though more recently the same group reported that Ezh2 acts in epithelial cells to promote fibrosis (45).…”
Section: Differential Expression Of Transcription Factors and Secretementioning
confidence: 99%